Idella : Marjorie Rawlings' "perfect maid" - Parker, Idella; Keating, Mary. (Gainesville : University Press of Florida, 1992)
Idella Parker's recollections of Marjorie Kinnan Rawlings are as intimate and frank as their ten years together. This long-awaited memoir, written by the black woman who was cook, housekeeper, and comfort to the famous author from 1940 to 1950, tells two stories - one of their spirited friendship, the other of race relations in rural Florida in the days before integration. Personal details - Marjorie's abandon behind the wheel of her cream-colored Oldsmobile, her boiled.
Egg for breakfast, her shoe size, and her penchant for wearing mismatched ankle socks - accompany accounts of visits from Julia Scribner and Zora Neale Hurston, of Marjorie's unconventional marriage to Norton Baskin, and of their moves back and forth from Cross Creek to St. Augustine, Florida, and to Van Hornesville, New York. Idella describes Marjorie's work habits on the porch at Cross Creek - as time went by, she notes, a whiskey bottle, wrapped in a paper bag, often.
Sat alongside the typewriter. By turns kind and generous, moody and depressed, Rawlings emerges as a woman of contrasts - someone "with few friends and many visitors ... who seldom smiled." Promises to stop drinking were made and broken repeatedly, and Rawlings' emotional demands on Idella escalated. Idella quit working for her three times, leaving for good three years before Rawlings' death. "I loved her then, and I love her still, but what could I do?" she asks.
Idella's own life is part of this memoir, too, as she describes her courtship and marriage, her family lineage back to Nat Turner, and what it was like to grow up in a segregated society.
Includes index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Rawlings, Marjorie Kinnan, -- 1896-1953 -- Friends and associates; Parker, Idella; Parker, Idella; Rawlings, Marjorie Kinnan, -- 1896-1953; Parker, Idella; Rawlings, Marjorie Kinnan; Women household employees -- United States -- Biography; Women authors, American -- 20th century -- Biography; Florida -- Biography; Employées de maison -- États-Unis -- Biographies; Écrivaines américaines -- 20e siècle -- Biographies; Floride -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- American -- General; Friendship; Women authors, American; Women household employees; Florida; United States; Autobiografie; Biografie; American Literature; English; Languages & Literatures; 1900-1999; Biographies